Clinical Comparative Study of Intravitreal Injection of Triamcinolone Acetonide and Aflibercept in the Treatment of Diabetic Retinopathy Cystoid Macular Edema - Yanxia Zhu; Jun Li; Songping Yu; Bangxun Mao; Jia Ying (Emergency Medicine International)
Objective To compare the curative effect of intravitreal injection of triamcinolone acetonide and aflibercept on diabetic retinopathy (DR) cystoid macular edema. Methods A total of 102 patients with DR cystoid macular edema admitted to the hospital were enrolled between July 2018 and July 2021. According to random number table method, they were divided into the control group (intravitreal injection of triamcinolone acetonide) and the observation group (intravitreal injection of aflibercept), 51 cases in each group. All were followed up for half a year. The clinical curative effect, visual acuity, central subfield macular thickness (CSMT), macular volume, scores of quality of life, and levels of cytokines in aqueous humor (vascular endothelial growth factor (VEGF), monocyte chemoattractant protein-1 (MCP-1), human angiopoietin-like protein 4 (ANGPTL4)] at different time points (before and at 6 months after surgery) were compared between the two groups. The times of drugs injection and occurrence of adverse reactions in both groups were statistically analyzed. Results The total effective rate in observation group was higher than that in the control group (96.08% vs 82.35%) (P<0.05). After 6 months of treatment, visual acuity was improved, and CSMT and macular volume were decreased in both groups. Also, the above changes were more significant in the observation group than those in the control group (P<0.05). After 6 months of treatment, levels of cytokines in aqueous humor were decreased in both groups. The levels of VEGF, MCP-1, and ANGPTL4 in observation group were lower than those in the control group (P<0.05). After 6 months of treatment, quality of life scores in observation group were higher than those in the control group (P<0.05). In the follow-up period, average times of drugs injection in the observation group were more than those in the control group, and the incidence of adverse reactions was lower than that in control group (5.88% vs 21.57%) (P<0.05). Conclusion The curative effect of intravitreal injection of both triamcinolone acetonide and aflibercept is good on DR cystoid macular edema. The curative effect of aflibercept is better, which can improve visual acuity and quality of life, and regulate cytokines in aqueous humor, with high safety. However, aflibercept has a high price, and further research is needed to determine whether its price can be matched with clinical benefits. In clinic, medication plan should be selected according to the actual situation.